Small Mammals - Faisal Ali, Anwarali Khan; Julius William, Dee; Muhd Amsyari, Morni; Nurul Farah Diyana, Ahmad Tahir; Sultana Parvin, Habeebur Rahman; Qhairil Shyamri, Rosli; Norfarhana, Mazlan; Roberta Chaya Tawie, Tingga; Mohd Ridwan, Abd Rahman; Isham, Azhar (UNIMAS Publisher, Sarawak Forestry Corporation Sdn Bhd, Natural History Publications (Borneo) Sdn. Bhd., 2022)
Situated at the western tip of Sarawak, Samunsam Wildlife Sanctuary is a Totally Protected Area within the state's legally protected areas, that aims to preserve the habitat of the Proboscis Monkey (Nasalis larvatus). The four major forest types within the Samunsam WS boundary include mangroves, riverine forests, Kerangas, and mixed dipterocarp forest (Bennett and Sebastian, 1988; Hazebroek and Abang Kashim, 2000). The area is home to many other elements of biodiversity, although previous studies in Samunsam WS have focussed on primates (four species: Aken and Kavanagh, 1982; Bennett, 1988; Rajaratnam, 1992; Kamaruzzaman et al., 2017; Mazlan et al., 2019) and birds (36 species: Long and Collar, 2002; Wilson, 2006).